2014
DOI: 10.1186/1752-1505-8-13
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of resilience and mental health outcomes of conflict-driven adult forced migrants

Abstract: BackgroundThe rising global burden of forced migration due to armed conflict is increasingly recognised as an important issue in global health. Forced migrants are at a greater risk of developing mental disorders. However, resilience, defined as the ability of a person to successfully adapt to or recover from stressful and traumatic experiences, has been highlighted as a key potential protective factor. This study aimed to review systematically the global literature on the impact of resilience on the mental he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
194
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(233 citation statements)
references
References 59 publications
10
194
1
6
Order By: Relevance
“…Nonetheless, it is likely that the outpatient treatment is similar in natives and immigrants as far as number and frequency of contacts are concerned, but that it may show differences regarding the type of intervention delivered, mainly as far as psychotherapeutic interventions is concerned, as suggested by Spinogatti et al [6]. In our sample, the time elapsed between migration and referral to the CMHC was consistent with the literature [27,28]. It is not clear whether its duration depends on the presence of socio-cultural barriers that hinder immigrants' access to psychiatric facilities, or instead on the accumulation of stressful events through the years, eventually leading to the onset of psychiatric symptoms and disorders.…”
Section: Bold Value Indicates the Statistically Significant Resultssupporting
confidence: 88%
“…Nonetheless, it is likely that the outpatient treatment is similar in natives and immigrants as far as number and frequency of contacts are concerned, but that it may show differences regarding the type of intervention delivered, mainly as far as psychotherapeutic interventions is concerned, as suggested by Spinogatti et al [6]. In our sample, the time elapsed between migration and referral to the CMHC was consistent with the literature [27,28]. It is not clear whether its duration depends on the presence of socio-cultural barriers that hinder immigrants' access to psychiatric facilities, or instead on the accumulation of stressful events through the years, eventually leading to the onset of psychiatric symptoms and disorders.…”
Section: Bold Value Indicates the Statistically Significant Resultssupporting
confidence: 88%
“…This finding is compatible with that of Siriwardhana et al (2014) and Hartley (2011) (44,45). Resilience is the capacity of an individual to demonstrate psychological health in a situation in which society views it as aversive (46).…”
Section: Discussionsupporting
confidence: 80%
“…The rising global burden of forced migration is increasingly recognised as an important issue in global and international public health (Siriwardhana, Sheik Ali, Roberts, & Stewart, 2014). There is some degree of evidence that children and young people from a refugee background have greater vulnerability to the development of mental health problems and to suicidal behaviour (Vijayakumar & Jotheeswaran, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Low or 'lower than expected' levels of service use may in part reflect reduced levels of need for service and a great degree of resilience (e.g. (Siriwardhana et al, 2014;Steel, Silove, Chey, Bauman, & Phan, 2005;Weine et al, 2000)). Nevertheless, studies that have measured mental health needs and service utilisation levels have found that the majority of young refugees who have significant mental health needs do not access services (e.g., (Bean, Eurelings-Bontekoe, Mooijaart, & Spinhoven, 2006;Ziaian, 2013).…”
Section: Introductionmentioning
confidence: 99%